2016
DOI: 10.5815/ijwmt.2016.04.07
|View full text |Cite
|
Sign up to set email alerts
|

Critical Analysis of Distributed Localization Algorithms for Wireless Sensor Networks

Abstract: In the past decade, Wireless sensor networks (WSNs) have attracted very much attention from the research and industrial community. Various WSN based projects produced fruitful and interesting results. In various applications, the location information of node is vital for the service. The reason is that users usually need to know what happens, but also where the concerned events happen. For example, in battlefield surveillance, the knowledge of where the enemy comes from can be much more important than only kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Various metaheuristic techniques have been implemented for enhancing the localization technique to raise the accuracy of actual localization method. Singh et al [10] employed an enhanced method for localization and later, utilized PSO method to determine the outcomes. Zhao et al [11] presented a localization technique depending upon hybrid chaotic approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Various metaheuristic techniques have been implemented for enhancing the localization technique to raise the accuracy of actual localization method. Singh et al [10] employed an enhanced method for localization and later, utilized PSO method to determine the outcomes. Zhao et al [11] presented a localization technique depending upon hybrid chaotic approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Three anchor nodes as the center to construct three squares are applied, in which the shadow area of the intersection of three squares is the overall workable area of the unknown nodes, and the initial population is generated randomly in the functional area. Singh et al applied an improved algorithm for localization and then used particle swarm optimization to refine the results [36]. Zhao et al proposed an improved localization algorithm based on hybrid chaotic strategy [10].…”
Section: Related Workmentioning
confidence: 99%
“…Research Article [1] authors have reported the different varieties of localization algorithms based on various estimations. The comparative analysis was made and concluded each schemes with features.…”
Section: Eai Endorsed Transactions On Energy Web and Information Techmentioning
confidence: 99%